Rapid assessment of malnutrition based on GLIM diagnosis in Crohn’s disease - Huang, Longchang; Niannian, Fu; Zhang, Yupeng; Shi, Yifan; Gao, Xuejin; Zhang, Li; Wu, Yan; Dai, Cong; Huang, Yuhong; Cao, Qian; Zhou, Wei; Jiang, Haitao; et al. (Frontiers in Nutrition, 2023)
Background and aims Malnutrition is strongly linked to adverse outcomes in patients with Crohn’s disease (CD). In this study, our objective was to validate the Global Leadership Initiative on Malnutrition (GLIM) criteria and develop a fast and accurate diagnostic approach for identifying malnutrition in CD patients. Methods This study assessed 177 CD patients from four general hospitals. The efficacy of the GLIM criteria for the diagnosis of CD malnutrition was compared. By analyzing the independent factors, a nomogram model was derived and internally validated to predict the diagnosis of malnutrition in patients with CD. Model performance was assessed using discrimination and calibration, decision curves, and net benefit analyses. Results Compared with the SGA criteria, the GLIM criteria was consistent in sensitivity (88.89%) and specificity (78.43%) [AUC = 0.84; 95% Confidence Interval (CI): 0.77–0.89]. The Harvey-Bradshaw index(HBI) score (OR: 1.58; 95% CI: 1.15–2.18), body mass index (OR: 0.41; 95% CI: 0.27–0.64), and mid-upper arm circumference (OR: 0.68; 95% CI: 0.47–0.9) were independent factors associated with malnutrition. The nomogram was developed based on these indicators showing good discrimination in malnutrition diagnosis (AUC = 0.953; 95% CI: 0.922–0.984), with agreement after calibration curve and decision curve analysis. Conclusion The GLIM criteria are appropriate for diagnosing malnutrition in CD patients. The HBI score may be used to diagnose malnutrition in patients with CD and become a possible selection for the GLIM etiologic criteria of inflammation. The HBM nomogram could be a simple, rapid, and efficient method for diagnosing malnutrition in CD patients.